Using Common Fate Model in Examining Dyadic Therapeutic Presence and Session Quality with Working Alliance as a Mediator - (:unkn) unknown (My University, 2025)
This study aimed to explore how therapeutic presence contributes to the development of the working alliance and overall session quality. The dataset comprised 15,145 sessions conducted by 409 master’s-level trainee therapists with 2,242 clients in China. After each session, both therapists and clients completed measures assessing therapeutic presence, working alliance, and session quality. Results showed that: (a) from both client and therapist perspectives, therapeutic presence temporally predicted working alliance across the course of treatment—higher therapeutic presence at one session led to stronger working alliance at the subsequent session, but not vice versa. (b) Shared perceptions of therapeutic presence between therapist and client predicted their shared perceptions of session quality at both the between-session and between–therapist-client dyad levels. (c) Therapists’ and clients’ individual perception of therapeutic presence was positively related to their individual perception of session quality at the between-session and between therapist-client dyad levels, respectively. (d) Therapist-client shared perception of working alliance did not mediate the relationship between their shared perception of therapeutic presence and session quality at the between-session level.
Keywords: Counseling psychology; common fate model; cross-lagged panel model; session quality; therapeutic presence; working alliance